Dental compositions comprising components comprising resorcinol or catechol moieties and uses thereof
By using low viscosity, high refractive index polymerizable component A1 in dental filler materials, combined with resin matrix and filler system, the balance problem of dental materials between hardness and flexibility is solved, and the use of bisphenol A is avoided. A dental composition with safe, beautiful appearance and good physical-mechanical properties is achieved.
Patent Information
- Application Number
- CN202380035620.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-26
- Filing Date
- 2023-03-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-03-29
AI Technical Summary
Existing dental fillers are difficult to find a balance between hardness and flexibility, resulting in potential fragility under chewing force, and some of the materials contain bisphenol A, affecting health and safety.
A dental composition has been developed, including a resin matrix, an initiator system and a filler system, where the polymerizable component A1 used in the resin matrix has low viscosity, high refractive index and hydrophobicity, and is independent of bisphenol A, which can be used without Easy to handle in a cured state and provides sufficient physical-mechanical properties upon hardening.
The dental composition has sufficient flexural strength, curing depth and aesthetics after hardening, while avoiding the use of bisphenol A, ensuring the safety and health of the material.
Smart Images

Figure BDA0005095866500000041 
Figure BDA0005095866500000042 
Figure BDA0005095866500000121
Abstract
Description
Technical Field
[0001] The present invention relates to a composition comprising a resin matrix, an initiator system and a filler system. The resin matrix comprises a polymerizable component comprising a backbone comprising a resorcinol or catechol moiety.
[0002] The composition is particularly useful in the dental and orthodontic fields, for example as a dental filling material having advantageous properties.
[0003] The dental compositions can also be used to produce mill blanks and as resins in laminate manufacturing processes. Background Art
[0004] Different dental filling materials are known for restorative purposes, including amalgam and dental composites.
[0005] In order to fulfil their primary function (replacing lost tooth structure), dental filling materials need to have adequate physical properties. In particular, they must have sufficient strength to be able to absorb and resist chewing forces.
[0006] However, if the material is too hard, it will also become more brittle.
[0007] Therefore, dental filling materials need not only to be hard enough but also to be flexible to some extent.
[0008] To meet these requirements, commercially available dental composite filling materials generally contain a certain amount of resin matrix, filler and initiator.
[0009] A widely used polymerizable (meth)acrylate component contained in the resin matrix is bisphenol A-glycidyl methacrylate (Bis-GMA) or other bisphenol-based (meth)acrylate monomers.
[0010] Compositions containing bisphenol-based monomers are said to possess a variety of advantageous properties such as high compressive strength, thus enabling practitioners to formulate a variety of different dental compositions for restorative purposes.
[0011] However, some literature seems to indicate that bisphenol-based monomers are not always recommended for all purposes. There is therefore a need for alternative polymerizable (meth)acrylate components.
[0012] US 2010 / 076115 A1 (Heraeus Kulzer) relates to compositions for dental composites which contain acrylic esters of tricyclo[5.2.1.02.6]decane having urethane groups.
[0013] US 3,853,962 (Gander) relates to dental restorative cements comprising the methacrylate monomer 1,3-bis[2,3-di(methacryloyloxy)-propoxy]-benzene. Restorative compositions containing this monomer are said to have improved compressive strength and related physical properties.
[0014] No. 4,744,827 (Winkel) describes (meth)acrylic acid derivatives of tricyclodecane which exhibit relatively little polymerization shrinkage.
[0015] US 8,426,490 B2 (Bissinger et al.) describes methacrylate-based monomers containing urethane bonds which exhibit well-balanced properties with respect to viscosity, refractive index, molecular weight and shrinkage values.
[0016] US 2011 / 0315928 A1 (Jin et al.) relates to a low viscosity and low stress dental composition comprising at least one low stress polymerizable resin and at least one filler. The dental composition is said to have a high cure depth and self-leveling properties and can be applied in bulk.
[0017] WO 2012 / 106083 A1 (3M) describes a dental composition comprising a hardenable compound containing relatively rigid backbone units, spacer units and units containing polymerizable end groups, the relatively rigid backbone units comprising aromatic or aliphatic cyclic moieties. The composition can be used in the dental field to provide, for example, a composite material with reduced brittleness. Summary of the invention
[0018] There remains a need for compositions having improved properties that are useful in the dental and orthodontic fields.
[0019] The composition should be easy to handle in its uncured state, in particular easy to apply to the surface to be treated.
[0020] This is also desirable if the composition allows for high filler loadings, if desired.
[0021] These properties should be achievable without the use of bisphenol A (BPA) containing monomers.
[0022] Ideally, after hardening the composition, the composition should have adequate physical-mechanical properties, such as adequate flexural strength and depth of cure.
[0023] Furthermore, if possible, the polymerizable components of the curable composition should have sufficient refractive index for desired aesthetics and depth of cure properties.
[0024] One or more of these objectives are achieved by the present invention as described in the text and claims.
[0025] In one embodiment, the invention features a dental composition comprising a) a resin matrix, b) an initiator system, c) a filler system, the resin matrix comprising a polymerizable component A1 characterized by any of the following formulas I, II or III
[0026]
[0027] in
[0028] X = independently selected from H, alkyl, I, Br, Cl; Z = independently selected from H, CH3, CH2OH; n, m = independently selected from integers ranging from 1 to 10; (m+n) = 1 to 10, or 2 to 8, or 2 to 6; R = independently selected from H, CH3;
[0029]
[0030] Wherein X = independently selected from H, alkyl, I, Br, Cl; Z = independently selected from H, CH3, CH2OH; k, n, m = independently selected from integers in the range of 1 to 10; (k+m+n) = 1 to 15, or 2 to 10, or 3 to 8; R = independently selected from H, CH3;
[0031] and mixtures thereof, as described herein and in the claims.
[0032] Additional embodiments of the invention are directed to a kit comprising a dental composition as described herein and in the claims and the following items, alone or in combination: a dental adhesive; a dental primer; a dispensing device; a polishing apparatus; a dental curing light, as described herein and in the claims.
[0033] The dental compositions described herein may also be used to produce dental restorations, dental mill blanks or as resin in a laminate manufacturing process as described herein and in the claims.
[0034] The dental compositions may also be used as composite filling materials, fixing materials for orthodontic appliances, cavity liners, or sealants.
[0035] In another embodiment, the invention is directed to a dental composition for use in a method of treating hard dental tissue in a mammalian mouth, the method comprising the steps of applying the dental composition to the surface of the hard dental tissue and hardening the dental composition as described herein and in the claims.
[0036] Also described are packaging devices comprising the compositions described herein and in the claims.
[0037] Unless defined differently, for the purpose of this specification, the following terms shall have the given meanings:
[0038] A "hardenable or curable or polymerizable component" is any component that can be cured or solidified by a hardening reaction, in particular by polymerization initiated by radiation in the presence of a photoinitiator. The hardenable component may contain only one, two, three or more polymerizable groups. Typical examples of polymerizable groups include unsaturated carbon groups, such as vinyl groups, which are particularly present in (meth)acrylate groups.
[0039] As used herein, "hardening" or "curing" a composition are used interchangeably and refer to a polymerization and / or cross-linking reaction involving one or more materials contained in the composition, including, for example, photopolymerization and chemical polymerization techniques (e.g., ionic reactions or chemical reactions that form free radicals effective to polymerize ethylenically unsaturated compounds).
[0040] "Radiation curable" shall mean that the component (or composition, as the case may be) can be cured by applying radiation (preferably electromagnetic radiation having a wavelength in the visible spectrum) under ambient conditions and within a reasonable time frame (e.g., within about 15, 10 or 5 minutes).
[0041] The term "visible light" is used to refer to light having a wavelength of 400 to 700 nanometers (nm).
[0042] As used herein, "(meth)acryloyl" is a shorthand term that refers to "acryloyl" and / or "methacryloyl." For example, a "(meth)acryloyloxy" group is a shorthand term that refers to an acryloyloxy group (i.e., CH2=CH-C(O)-O-) and / or a methacryloyloxy group (i.e., CH2=C(CH3)-C(O)-O-).
[0043] The "resin matrix" comprises all hardenable compounds (monomers, oligomers and / or polymers) present in the hardenable composition. The resin may comprise only one hardenable compound or a mixture of different hardenable compounds.
[0044] The "filler system" comprises all fillers present in the hardenable composition. Only one type of filler or a mixture of different fillers may be used.
[0045] "Nanosized fillers" are fillers whose individual particles have a size in the nanometer range, for example an average particle size of less than 100 nm or less than 50 nm. Useful examples are given in US 6,899,948 (Zhang et al.) and US 6,572,693 (Wu et al.).
[0046] "Particle" means a solid substance having a geometrically definable shape. The shape may be regular or irregular. Particles can generally be analyzed with respect to, for example, particle size and particle size distribution.
[0047] As used herein, "aggregated" describes a strong association of particles that are typically bound together by, for example, residual chemical treatment or partial sintering. The specific surface area of the aggregated particles is typically smaller than the specific surface area of the primary particles that make up the aggregate (see DIN 53206; 1972).
[0048] An "initiator or initiator system" is a component or combination of components that is capable of initiating the curing process of a hardenable component.
[0049] "Dispersed within the resin" means that the filler particles are present in the resin as discrete, non-associated (ie, non-agglomerated and non-aggregated) particles.
[0050] A "dental composition" is any composition which can be used or is intended to be used in the dental field. In this respect, the composition should be harmless to the patient's health and therefore contain no hazardous and toxic components which could migrate out of the composition.
[0051] Possible uses of the dental compositions are as or for the production of permanent and temporary crown and bridge materials, artificial crowns, dental filling materials, cavity liners, coating compositions, sealants, mill blanks, laboratory materials and orthodontic devices.
[0052] The dental composition is typically a hardenable composition that can be hardened under ambient conditions, including a temperature range of 15°C to 50°C or 20°C to 40°C, within a time range of 30 minutes, or 20 minutes, or 10 minutes.
[0053] Higher temperatures are not recommended as they may cause pain to the patient and may be harmful to the patient's health.
[0054] Dental compositions are typically provided to the practitioner in a relatively small volume (ie, a volume in the range of 0.1 ml to 100 ml, or 0.5 ml to 50 ml, or 1 ml to 30 ml).
[0055] "Dental article" means an article to be used in the dental field, in particular as or for the production of a dental restoration. A dental article generally has two distinct surface parts, an outer surface and an inner surface. The outer surface is the surface which is generally not in permanent contact with the tooth surface. In contrast, the inner surface is the surface which is used to attach or fix the dental article to the tooth. If the dental article has the shape of a crown, the inner surface generally has a concave shape, while the outer surface generally has a convex shape. Dental articles should not contain components which are harmful to the patient's health and therefore do not contain hazardous and toxic components which could migrate out of the dental or orthodontic article.
[0056] "Dental restoration" means a dental article used to repair a tooth to be treated. Examples of dental restorations include crowns, bridges, inlays, onlays, veneers, facings, copings, crown-bridge frameworks, and parts thereof.
[0057] By "dental mill blank" is meant a solid block of material (three-dimensional article) from which a dental article can be processed. A dental mill blank generally has a geometrically defined shape. A dental mill blank may have a size of 20 mm to 30 mm in two dimensions, for example may have a diameter within this range, and may have a length in the third dimension. A block or blank for making a single crown may have a length of 15 mm to 30 mm, and a block or blank for making a bridge may have a length of 40 mm to 80 mm.
[0058] In addition to the above dimensions, dental mill blanks can also have the shape of a cube, cylinder or cuboid. If more than one crown or bridge is to be manufactured from one blank, a larger milling block may be advantageous. For these cases, the diameter or length of the cylindrical or cuboid mill blank can be in the range of 80 mm to 200 mm and the thickness in the range of 10 mm to 30 mm.
[0059] “Orthodontic appliances” include orthodontic brackets, buccal tubes, lingual retainers, orthodontic bands, bite openers, buttons, and splints.
[0060] "Additive manufacturing" or "3D printing" refers to a process that involves creating an object layer by layer from digital data. The article can be of almost any shape or geometry and is produced from a three-dimensional model or other electronic data source.
[0061] There are many 3d printing technologies, one of which is vat polymerization that uses a radiation curing step to make three-dimensional articles. Examples of vat polymerization technologies include stereolithography (SLA) and digital light processing (DLP).
[0062] "Stereolithography" is an example of a layer-by-layer manufacturing technique, where a laser beam is aimed across the print area, typically using two motors, thereby solidifying the print resin. The process breaks down the design layer by layer into a series of dots.
[0063] "Digital light processing" is another example of an additive manufacturing technique, and typically involves using a digital projector screen to flash an image of each layer onto the build platform of the additive manufacturing unit. This image is typically made up of square pixels, resulting in a layer formed of small rectangular bricks called voxels.
[0064] "Environmental conditions" means the conditions to which the compositions described in this text are typically subjected during storage and handling. Environmental conditions can be, for example, a pressure of 900 to 1,100 mbar, a temperature of 10°C to 40°C, and a relative humidity of 10% to 100%. In the laboratory, environmental conditions are typically adjusted to 20°C to 25°C and 1,000 to 1,025 mbar (at sea level).
[0065] As used herein, "a", "an", "the", "at least one", and "one or more" are used interchangeably. Also herein, numerical ranges recited by endpoints include all numbers contained within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0066] Adding "plural" to a term means that the term shall include both the singular and the plural. For example, the term "additive" refers to one additive and multiple additives (eg, 2, 3, 4, etc.).
[0067] The terms "comprises" or "comprising" and variations thereof do not have a limiting meaning when these terms appear in the specification and claims. "Consisting essentially of means that certain additional components may be present, i.e., those components that do not materially affect the basic characteristics of the article or composition. "Consisting of means that no additional components should be present. The term "comprising" shall also include the terms "consisting essentially of" and "consisting of."
[0068] A composition is "substantially or substantially free of" a component if the composition does not contain the component as an essential feature. Thus, the component itself is not intentionally added to the composition, or the component is not intentionally added to the composition together with other components or ingredients of other components. A composition that is substantially free of a component generally does not contain the component at all. However, sometimes the presence of a small amount of the component is unavoidable, for example due to impurities contained in the raw materials used. "Substantially free" generally means an amount of less than 1%, 0.5% or 0.1% by weight. DETAILED DESCRIPTION
[0069] The compositions and methods described herein have been found to have several advantageous properties.
[0070] The di- and / or trifunctional (meth)acrylate components exhibit a high refractive index and a relatively low viscosity.
[0071] A high refractive index can contribute to the curing properties and aesthetics of the cured dental composition.
[0072] Due to the low viscosity, these (meth)acrylate components can be easily incorporated into the resin matrix and mixed with other components such as fillers, even at high filling rates.
[0073] Low viscosity, flowable compositions can now be formulated.
[0074] Furthermore, these components are found to be suitable replacements for bisphenol A derived components, which are commonly used in dental preparations. Bisphenol A derived components mean components containing a bisphenol A moiety.
[0075] Compositions containing these components exhibit advantageous mechanical properties, such as low polymerization shrinkage stress, improved tensile and flexural strengths, and sufficient depth of cure.
[0076] The composition also exhibits favorable cusp deflection values after curing (ie, low deformation of the aluminum block upon curing of a standardized filling).
[0077] The present invention relates to compositions useful in the dental and orthodontic fields.
[0078] The composition comprises a resin matrix, an initiator system, a filler system and optionally other components such as diluents and adjuvants.
[0079] The resin matrix contains a polymerizable component A1, and may contain an additional polymerizable component different from the polymerizable component A1.
[0080] Component A1 is found to generally contribute to or exhibit at least one or more of the following properties.
[0081] Component A1
[0082] a) generally have good filler wettability. This may be beneficial for achieving relatively high filler loadings if desired;
[0083] b) generally have a relatively low viscosity (e.g., 2.0 Pa*s to 40 Pa*s, or 2.0 Pa*s to 30 Pa*s; 23°C; shear rate: 100 s -1 ). This may be beneficial to achieve proper processing of the final composition, if desired. Increasing the amount of filler may also be beneficial, if desired, as the viscosity of the final composition will generally be within an acceptable range;
[0084] c) generally have a relatively high refractive index (e.g., 1.520 to 1.565 or 1.530 to 1.560 (n D 20 )). This may be beneficial to achieve appropriate aesthetics and / or high cure depth of the photocurable material, if desired;
[0085] d) generally have a relatively high hydrophobicity. This may be beneficial for achieving relatively low water absorption and / or exogenous staining, if desired;
[0086] e) can be used to provide a composition showing reduced brittleness of the cured composition (ie relatively high impact strength and / or moderate E-modulus). This may be beneficial if the risk of failure due to cracks and / or fractures should be reduced.
[0087] f) can be used to provide compositions that exhibit a high depth of cure. This can be beneficial if batch curing applications of photocurable materials are desired.
[0088] Component A1 can be described as a component comprising a main chain unit comprising a di- or trihydroxybenzene moiety; and two or three spacer units connected to the main chain unit via an ether bond, the spacer unit comprising the structural element -CH2-CH-CH2-; comprising two or three (meth)acrylate moieties, which are attached to the main chain via an alkyleneoxy moiety; comprising two or three phenoxy moieties as side groups attached to the main chain through the spacer units; and not comprising a urethane moiety.
[0089] The molecular weight of component A1 is generally in the range of 500 g / mol to 1,200 g / mol.
[0090] Examples of component A1 include
[0091]
[0092]
[0093] in
[0094] m, n, k = integers independently selected from the range of 1 to 10,
[0095] and (m+n)=1 to 10, or
[0096] (m+n+k)=1 to 15,
[0097] and mixtures thereof.
[0098] The molecules of component A1 can generally be produced by reacting a phenolic compound (e.g., resorcinol or catechol), a glycidyl phenyl ether compound, and ethylene carbonate to produce an alkoxylated intermediate compound, which is hydrolyzed to produce an ethoxylated intermediate compound, which is further reacted with (meth)acrylic acid.
[0099] Component A1 is typically present in the composition in the following amounts: at least 3 wt%, 5 wt% or 8 wt%; up to 50 wt%, 40 wt% or 30 wt%; ranging from 3 wt% to 50 wt%, or from 5 wt% to 40 wt%, or from 8 wt% to 30 wt%; the wt% being relative to the weight of the entire composition.
[0100] The resin matrix may comprise further polymerizable components different from component A1. One or more of these further polymerizable components may be present.
[0101] These further polymerizable components are referred to as component A2.
[0102] Suitable components A2 contain at least one ethylenically unsaturated bond and are capable of addition polymerization.
[0103] Suitable polymerizable components may be characterized by the formula:
[0104] A n BA m
[0105] wherein A is an ethylenically unsaturated group, such as a (meth)acryloyl moiety,
[0106] B is selected from (i) a linear or branched C1 to C2 optionally substituted by other functional groups (e.g., halogen (including Cl, Br, I), OH or a mixture thereof); 12 (ii) a C6 to C16 alkyl group optionally substituted with other functional groups (e.g., halogen, OH or a mixture thereof); 12 aryl, or (iii) an organic group having 4 to 20 carbon atoms bonded to one another via one or more ether, thioether, ester, thioester, thiocarbonyl, amide, carbamate, carbonyl and / or sulfonyl bonds,
[0107] m, n are independently selected from 0, 1, 2, 3, 4, 5 or 6, provided that n+m is greater than 0, ie, at least one A group is present.
[0108] Such polymerizable materials include mono-, di- or polyacrylates and methacrylates such as methyl acrylate, methyl methacrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-hexyl (meth)acrylate, stearyl (meth)acrylate, allyl (meth)acrylate, glycerol di(meth)acrylate, diurethane dimethacrylate known as UDMA which is a reaction product of 2-hydroxyethyl methacrylate (HEMA) and 2,2,4-trimethyl-hexamethylene diisocyanate (TMDI) (a mixture of isomers, e.g., Plex 6661-0), glycerol tri(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,3-propylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,2,4-butanetriol tri(meth)acrylate esters, 1,4-cyclohexanediol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, sorbitol hexa(meth)acrylate, bis[1-(2-(meth)acryloyloxy)]-p-ethoxy-phenyldimethylmethane and trihydroxy-ethyl-isocyanurate trimethacrylate; diacrylate and dimethacrylate of polyethylene glycol having a molecular weight of 200 to 500, copolymerizable mixtures of acrylated monomers (see, for example, US 4,652,274) and acrylated oligomers (see, for example, US 4,642,126); and vinyl compounds such as styrene, divinyl succinate, divinyl adipate and divinyl phthalate; polyfunctional (meth)acrylates containing urethane, urea or amide groups. If desired, mixtures of two or more of these free radical polymerizable materials can be used.
[0109] If desired, an addition fragmentation monomer (AFM) may also be added. The addition fragmentation monomer may be characterized by the formula:
[0110]
[0111] in
[0112] R 1 , R 2 and R 3 Each independently is Z m -Q-, a (hetero)alkyl group or a (hetero)aryl group, provided that R 1 , R 2 and R 3 At least one of them is Z m -Q-; Q is a linking group with a valence of m+1; Z is an ethylenically unsaturated polymerizable group; m is 1 to 6; each X 1 are independently -O- or -NR 4 -, where R 4 is H or C1-C4 alkyl; and n is 0 or 1.
[0113] These monomers are said to have lower stress. Suitable monomers are also described in US 9,056,043 (Joly et al.).
[0114] Monomers containing hydroxyl moieties may also be added. Suitable compounds include 2-hydroxyethyl (meth)acrylate (HEMA), 2- or 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, dialkylene glycol mono(meth)acrylate (e.g., diethylene glycol mono(meth)acrylate, triethylene glycol mono(meth)acrylate, tetraethylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, dipropylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate), and further, 1,2- or 1,3- and 2,3-dihydroxypropyl (meth)acrylate, 2-hydroxypropyl-1,3-di(meth)acrylate, 3-hydroxypropyl-1,2-di(meth)acrylate, N-(meth)acryloyl-1,2-dihydroxypropylamine, N-(meth)acryloyl-1,3-dihydroxypropylamine, an adduct of phenol and glycidyl (meth)acrylate (e.g., 1-phenoxy-2-hydroxypropyl (meth)acrylate), 1-naphthyloxy-2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate and 2,3-dihydroxypropyl (meth)acrylate are particularly preferred. If desired, a mixture of one or more of these components may be used.
[0115] Component A2 is typically present in the composition in an amount of at least 0 wt%, 1 wt% or 5 wt%; at most: 60 wt%, 50 wt% or 40 wt%; ranging from 0 wt% to 60 wt%, 1 wt% to 50 wt%, or 5 wt% to 40 wt%; the wt% being relative to the entire composition.
[0116] The compositions described in this text include an initiator system.
[0117] Initiator systems are able to start the curing process of the hardenable components present in the resin matrix.For curing one-component compositions, photoinitiator systems are usually used.
[0118] Suitable photoinitiator systems for free-radical polymerization are generally known to those skilled in the art of processing dental materials.
[0119] Suitable photoinitiator systems typically contain a sensitizer comprising an alpha-alpha diketone moiety, an anthraquinone moiety, a thioxanthone moiety, or a benzoin moiety. Sensitizers containing an alpha-alpha diketone moiety are generally preferred.
[0120] A typical photoinitiator system comprises a combination of a sensitizer and a reducing agent or donor component, which is generally referred to as a photoinitiator system.
[0121] As the sensitizer, those which can polymerize the polymerizable monomer by the action of visible light having a wavelength of 390 nm to 830 nm are preferred.
[0122] Examples of sensitizers that can be used include camphorquinone, benzil, diacetyl, benzyl dimethyl ketal, benzyl diethyl ketal, benzyl di(2-methoxyethyl) ketal, 4,4,'-dimethylbenzyl dimethyl ketal, anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1,2-benzanthraquinone, 1-hydroxyanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, 1-bromoanthraquinone, thioxanthone, 2-isopropylthioxanthone, 2-nitrothioxanthone, 2-Methylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 2-chloro-7-trifluoromethylthioxanthone, thioxanthone-10,10-dioxide, thioxanthone-10-oxide, benzoin methyl ether, benzoin ethyl ether, isopropyl ether, benzoin isobutyl ether, benzophenone, bis(4-dimethyl-amino-phenyl)ketone, 4,4,'-bisdiethylamino-benzophenone.
[0123] As the reducing agent or donor component, a tertiary amine or the like is generally used. Suitable examples of the tertiary amine include N,N-dimethyl-p-toluidine, N,N-dimethyl-aminoethyl methacrylate, triethanolamine, 4-dimethylaminobenzoic acid methyl ester, 4-dimethyl-aminobenzoic acid ethyl ester, methyldiphenylamine, and 4-dimethylaminobenzoic acid isopentyl ester.
[0124] Additional suitable reducing agents include diarylalkylamines characterized by the formula: Ar 1 Ar 2 RN, of which Ar 1 and Ar 2 Independently selected from phenyl or alkyl (e.g., C1 to C4) substituted phenyl, R is an alkyl (e.g., C1 to C4) group, wherein one or more H atoms may be substituted by halogen, and N is nitrogen. These reducing agents are described in more detail in US 8,314,162 (Hailand et al.).
[0125] In addition, a sensitizer, an electron donor and Ternary photopolymerization initiation systems composed of salts, such as those described in US 6,187,833 (Oxman et al.), US 6,025,406 (Oxman et al.), US 6,043,295 (Oxman et al.), US 5,998,495 (Oxman et al.), US 6,084,004 (Weinmann et al.), US 5,545,676 (Palazzotto et al.), US 8,314,162 B2 (Hailand et al.) and US 6,765,036 (Dede et al.).
[0126] In the ternary photoinitiator system, the first component is Iodine is preferred Salt, i.e. diaryliodonium Salt.
[0127] iodine The salt is preferably soluble in the monomer and storage stable (ie, does not spontaneously promote polymerization) when dissolved therein in the presence of the sensitizer and the donor. The choice of salt may depend to some extent on the particular monomer, polymer or oligomer, sensitizer and donor selected. Suitable iodine Salts are described in US 3,729,313, US 3,741,769, US 3,808,006, US 4,250,053 and US 4,394,403. Iodine The salt may be a simple salt (e.g., containing an anion such as Cl - Br - ,I - or C4H5SO3 - ) or metal complex salts (e.g., containing SbF5OH - or AsF6 - ). If necessary, iodine can be used A mixture of salts. Preferably iodine Salts including diphenyl iodide Salts such as diphenyl iodide Chloride, diphenyl iodide Hexafluorophosphate and diphenyl iodide Tetrafluoroborate.
[0128] The second component in the ternary photoinitiator system is the sensitizer.
[0129] The sensitizer is desirably soluble in the monomer and capable of light absorption in the wavelength range of greater than 400 nm to 1,200 nm, more preferably greater than 400 nm to 700 nm, and most preferably greater than 400 nm to 600 nm.
[0130] Suitable sensitizers may include compounds from the following classes: ketones, coumarin dyes (e.g., ketocoumarins), xanthene dyes, acridine dyes, thiazole dyes, thiazine dyes, oxazine dyes, azine dyes, aminoketone dyes, porphyrins, aromatic polycyclic hydrocarbons, para-substituted aminostyryl ketone compounds, aminotriarylmethanes, merocyanines, squarylium dyes, and pyridines. Dyes. Ketones (eg, monoketones or α-diketones), ketocoumarins, amino aromatic ketones and p-substituted aminostyryl ketone compounds are preferred sensitizers.
[0131] For example, one preferred class of ketone sensitizers has the formula: ACO(X)b B, where X is CO or CR 5 R 6 , where R 5 and R 6 A and B may be the same or different and may be hydrogen, alkyl, alkaryl or aralkyl, b is zero or one, and A and B are different and may be substituted (with one or more non-interfering substituents) may be the same or unsubstituted aryl, alkyl, alkaryl or aralkyl groups, or A and B together may form a cyclic structure which may be a substituted or unsubstituted alicyclic, aromatic, heteroaromatic or fused aromatic ring.
[0132] Suitable ketones of the above formula include monoketones (b=0), such as 2,2-, 4,4- or 2,4-dihydroxybenzophenone, di-2-pyridyl ketone, di-2-furanyl ketone, di-2-thienyl ketone, benzoin, fluorenone, chalcones, Michler's ketone, 2-fluoro-9-fluorenone, 2-chlorothioxanthone, acetophenone, benzophenone, 1- or 2-naphthylacetonone, 9-acetylanthracene, 2-, 3- or 9-acetyphenanthrene, 4-acetylbiphenyl, propiophenone, butyrophenone, valerophenone, 2-, 3- or 4-acetylpyridine, 3-acetylcoumarin, and the like. Suitable diketones include aralkyl diketones such as anthraquinone, phenanthrenequinone, o-, m- and p-diacetylbenzene, 1,3-, 1,4-, 1,5-, 1,6-, 1,7- and 1,8-diacetylnaphthalene, 1,5-, 1,8- and 9,10-diacetylanthracene, etc. Suitable α-diketones (b=1 and X=CO) include 2,3-butanedione, 2,3-pentanedione, 2,3-hexanedione, 3,4-hexanedione, 2,3-heptanedione, 3,4-heptanedione, 2,3-octanedione, 4,5-octanedione, benzil, 2,2'-3,3'- and 4,4'-dihydroxybenzil, furil, di-3,3'-indoleethyldione, 2,3-bornanedione (camphorquinone), biacetyl, 1,2-cyclohexanedione, 1,2-naphthoquinone, etc.
[0133] The third component of the ternary initiator system is the donor.
[0134] Preferred donors include, for example, amines (including aminoaldehydes and aminosilanes), amides (including phosphoramides), ethers (including thioethers), ureas (including thioureas), ferrocene, sulfinic acid and its salts, salts of ferrocyanide, ascorbic acid and its salts, dithiocarbamic acid and its salts, xanthates, ethylenediaminetetraacetates, and tetraphenylborate. The donor may be unsubstituted or substituted with one or more non-interfering substituents. Particularly preferred donors contain electron donor atoms, such as nitrogen, oxygen, phosphorus or sulfur atoms, and abstractable hydrogen atoms bonded to the alpha carbon or silicon atom of the electron donor atom. A variety of donors are disclosed in US 5,545,676. This reference is incorporated herein by reference.
[0135] Alternatively, free radical initiators useful in the present invention include acylphosphine oxides and bisacylphosphine oxides.
[0136] Suitable acylphosphine oxides can be described by the following general formula:
[0137] (R 9 )2-P(=O)-C(=O)—R 10
[0138] Each R 9 R is independently a hydrocarbon group such as alkyl, cycloalkyl, aryl and aralkyl, any of which may be substituted by a halogen, alkyl or alkoxy group, or both R 9 The groups may be joined to form a ring together with the phosphorus atom, and wherein R 10 is a hydrocarbon group, a five- or six-membered heterocyclic group containing S-, O- or N-, or -ZC(=O)-P(=O)-(R 9 )2 group, wherein Z represents a divalent hydrocarbon group such as an alkylene group or a phenylene group having 2 to 6 carbon atoms.
[0139] Preferred acylphosphine oxides are those in which R 9 and R 10 The groups are those of phenyl or phenyl substituted by lower alkyl or lower alkoxy. By "lower alkyl" and "lower alkoxy" are meant such groups having 1 to 4 carbon atoms. Examples can also be found in, for example, US 4,737,593.
[0140] Examples include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-ethoxy-phenyl-phosphine oxide, bis-(2,6-dichlorobenzoyl)-4-biphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2-naphthylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthyl ...4-ethoxyphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-biphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2-naphthylphosphine oxide, bis-(2 ,6-dichlorobenzoyl)-4-chlorophenyl-phosphine oxide, bis-(2,6-dichlorobenzoyl)-2,4-dimethoxy-phenyl-phosphine oxide, bis-(2,6-dichlorobenzoyl)decylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-octyl-phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethyl-phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,4,6-trimethylbenzoyl)-2,5-dimethyl-phenylphosphine oxide Phosphine, bis-(2,6-dichloro-3,4,5-trimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichloro-3,4,5-trimethoxybenzoyl)-4-ethoxyphenylphosphine oxide, bis-(2-methyl-1-naphthoyl)-2,5-dimethylphenylphosphine oxide, bis-(2-methyl-1-naphthoyl)phenylphosphine oxide, bis-(2-methyl-1-naphthoyl)-4-biphenylphosphine oxide, bis-(2-methyl-1-naphthoyl)-4-ethoxyphenylphosphine oxide, Bis-(2-methyl-1-naphthoyl)-2-naphthyl-phosphine oxide, bis-(2-methyl-1-naphthoyl)-4-propylphenylphosphine oxide, bis-(2-methyl-1-naphthoyl)-2,5-dimethylphosphine oxide, bis-(2-methoxy-1-naphthoyl)-4-ethoxy-phenyl-phosphine oxide, bis-(2-methoxy-1-naphthoyl)-4-biphenylphosphine oxide, bis-(2-methoxy-1-naphthoyl)-2-naphthylphosphine oxide and bis-(2-chloro-1-naphthoyl)-2,5-dimethylphenylphosphine oxide.
[0141] Tertiary amine reducing agents may be used in combination with the acylphosphine oxides. Exemplary tertiary amines useful in the present invention include ethyl 4-(N,N-dimethyl-amino)benzoate and N,N-dimethylaminoethyl methacrylate.
[0142] Commercially available phosphine oxide photoinitiators capable of free radical initiation when irradiated at wavelengths greater than 400 nm to 1,200 nm include a 25:75 by weight mixture of bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide and 2-hydroxy-2-methyl-1-phenylpropan-1-one (formerly known as Irgacure TM1700, Ciba), 2-benzyl-2-(N,N-dimethylamino)-1-(4-morpholinophenyl)-1-butanone (formerly known as Irgacure TM 369, Ciba), bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium (formerly known as Irgacure TM 784DC, Ciba), a 1:1 mixture by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2-hydroxy-2-methyl-1-phenylpropan-1-one (formerly known as Darocur TM 4265, Ciba), ethyl-2,4,6-trimethylbenzylphenylphosphine oxide (formerly known as Lucirin TM LR8893X, BASF), and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (formerly Irgacure TM 819, BASF).
[0143] Another free radical initiator system that may alternatively be used includes the class of ionic dye counterion complex initiators containing a borate anion and a complementary cationic dye.
[0144] Borate photoinitiators are described, for example, in US 4,772,530 (Gottschalk et al.), US 4,954,414 (Adair et al.), US 4,874,450 (Gottschalk), US 5,055,372 (Shanklin et al.), and US 5,057,393 (Shanklin et al.).
[0145] The borate anions useful in these photoinitiators may generally have the formula R 1 R 2 R 3 R 4 B - , where R 1 , R 2 , R 3 and R 4 R may independently be an alkyl group, an aryl group, an alkaryl group, an allyl group, an aralkyl group, an alkenyl group, an alkynyl group, an alicyclic group, and a saturated or unsaturated heterocyclic group. 2 , R 3 and R 4 is an aryl group and more preferably a phenyl group, and R 1 It is an alkyl group and more preferably a secondary alkyl group.
[0146] The cationic counterions can be cationic dyes, quaternary ammonium groups, transition metal coordination complexes, etc. The cationic dyes used as counterions can be cationic methylene, polymethylene, triarylmethylene, indoline, thiazine, xanthene, oxazine or acridine dyes. More specifically, the dyes can be cationic cyanine, carbocyanine, hemicyanine, rhodamine and azomethine dyes. Specific examples of useful cationic dyes include methylene blue, safranin O and malachite green. The quaternary ammonium groups used as counterions can be trimethylhexadecylammonium, cetylpyridinium and tetramethylammonium. Other organophilic cations can include pyridinium phosphonium and sulfonium.
[0147] The photosensitive transition metal coordination complexes that can be used include complexes of cobalt, ruthenium, osmium, zinc, iron and iridium with ligands such as pyridine, 2,2'-dipyridine, 4,4'-dimethyl-2,2'-dipyridine, 1,10-phenanthroline, 3,4,7,8-tetramethylphenanthroline, 2,4,6-tris(2-pyridyl-s-triazine) and related ligands.
[0148] In an alternative option, heat can be used to initiate the hardening or polymerization of the free radical active groups.
[0149] Examples of heat sources suitable for the dental materials of the present invention include induction, convection and radiation. The heat source should be able to generate a temperature of at least 40 °C to 15 °C under normal conditions or under elevated pressure.
[0150] The heat curing protocol is sometimes preferably used to initiate the polymerization of the material that occurs outside the oral environment, for example when the composition is used to produce grinding blanks or in the post-curing step of the article obtained by processing the composition into a resin by an additive manufacturing method.
[0151] The initiator system is generally present in the following amounts: at least 0.1 wt%, 0.2 wt% or 0.3 wt%; at most 4 wt%, 3 wt% or 2 wt%; in the range of 0.1 wt% to 4 wt%, 0.2 wt% to 3 wt%, or 0.3 wt% to 2 wt%; wt% based on the entire composition.
[0152] The compositions described in this text contain a filler system. The filler system can contain one filler or a mixture of different types of fillers.
[0153] Adding fillers may be beneficial for example to adjust rheological properties such as viscosity.
[0154] The size of the filler particles should be such that a uniform mixture with the hardenable components forming the resin matrix can be obtained.
[0155] The average particle size of the filler may be in the range of 5 nm to 50 μm. If desired, the measurement of the particle size of the filler particles may be performed as described in the Examples section.
[0156] The filler is typically a non-acid reactive filler. A non-acid reactive filler is a filler that does not undergo an acid / base reaction with an acid.
[0157] Useful non-acid-reactive fillers include fumed silica, fillers based on non-acid-reactive fluoroaluminosilicate glasses, quartz, ground glass, water-insoluble fluorides such as CaF2, silica gels such as silicic acid, especially fumed silicic acid and particles thereof, cristobalite, calcium silicate, zirconium silicate, zeolites, including molecular sieves.
[0158] Suitable fumed silicas include, for example, those sold under the trade name Aerosil TM Products sold in the series OX-50, -130, -150 and -200 are available from Evonik's Aerosil TM R8200, R805, CAB-O-SIL from Cabot Corp (Tuscola) TM M5, and HDK types from Wacker, such as HDK TM -H2000, HDK TM H15, HDK TM H18, HDK TM H20 and HDK TM H30.
[0159] Fillers that may also be used and provide radiopacity to dental materials include heavy metal oxides and fluorides. As used herein, "radiopacity" describes the ability to distinguish hardened dental materials from tooth structure in a conventional manner using standard dental X-ray equipment. Radiopacity of dental materials is advantageous in certain situations where X-rays are used to diagnose dental conditions. For example, a radiopaque material will allow detection of secondary caries that may have formed in the tooth tissue surrounding the filling.
[0160] Oxides or fluorides of heavy metals with atomic numbers greater than 28 may be preferred. Heavy metal oxides or fluorides should be selected so that undesirable colors or shades are not imparted to the hardened resin in which the heavy metal oxides or fluorides are dispersed. For example, iron and cobalt are disadvantageous because they impart dark and contrasting colors to the neutral tooth color of dental materials. More preferably, heavy metal oxides or fluorides are oxides or fluorides of metals with atomic numbers greater than 30. Suitable metal oxides are oxides of yttrium, strontium, barium, zirconium, hafnium, niobium, tantalum, tungsten, bismuth, molybdenum, tin, zinc, lanthanides (i.e., elements with atomic numbers in the range of 57-71 (including end values)), cerium, and combinations thereof. Suitable metal fluorides are, for example, yttrium trifluoride and ytterbium trifluoride. Most preferably, oxides and fluorides of heavy metals with atomic numbers greater than 30 but less than 72 are optionally included in the material of the present invention. Particularly preferred radiopaque metal oxides include lanthanum oxide, zirconium oxide, yttrium oxide, ytterbium oxide, barium oxide, strontium oxide, cerium oxide, and combinations thereof. The heavy metal oxide particles may be aggregated. If so, preferably, the average diameter of the aggregated particles is equal to or less than 200 nm.
[0161] Other suitable fillers for increasing radiopacity are barium and strontium salts, particularly strontium sulfate and barium sulfate.
[0162] Fillers that may also be used include nano-sized fillers such as nano-sized silica or a mixture of nano-sized silica and zirconium oxide particles. Suitable nano-sized particles typically have an average particle size in the range of 5 nm to 50 nm.
[0163] The preferred nano-sized silica is available under the trade name NALCO TM Colloidal silica was purchased from Nalco Chemical Co. (Naperville, Ill.) (e.g., preferred silica particles can be obtained using NALCO TMproducts 1040, 1042, 1050, 1060, 2327 and 2329), available from Nissan Chemical America Company, Houston, Texas (e.g., SNOWTEX-ZL, -OL, -O, -N, -C, -20L, -40 and -50); available from Admatechs Co., Ltd., Japan (e.g., SX009-MIE, SX009-MIF, SC1050-MJM and SC1050-MLV); available from Grace GmbH & Co. KG, Worms, Germany (e.g., available under the trade name LUDOX TM those available from Akzo Nobel Chemicals GmbH, Leverkusen, Germany (e.g., available under the trade name LEVASIL TM 50 / 50%, 100 / 45%, 200 / 30%, 200A / 30%, 200 / 40%, 200A / 40%, 300 / 30% and 500 / 15%), and those available from Bayer MaterialScience AG, Leverkusen, Germany (e.g., available under the trade name DISPERCOLL TM S obtained, such as 5005, 4510, 4020 and 3030).
[0164] Surface treatment of the filler particles prior to loading into the dental material can provide a more stable dispersion in the resin. Preferably, the surface treatment stabilizes the particles so that the particles will disperse well in the resin and produce a substantially homogeneous composition.
[0165] Suitable surface treatments or surface modifiers include silane treatments that are capable of polymerizing with the resin. Preferred silane treatments include γ-methacryloxypropyltrimethoxysilane (commercially available under the trade name A-174 (Momentive)) and γ-glycidoxypropyltrimethoxysilane (commercially available under the trade name G6720 (United Chemical Technologies (Bristol, Pa.)).
[0166] Thus, silica particles, as well as other suitable non-acid reactive fillers, may be treated with a resin compatible surface treatment agent.
[0167] Suitable fillers may also be characterized by the following properties, alone or in combination: Specific surface area (BET): 10 m 2 / g to 400m 2 / g, or 15m 2 / g to 300m 2 / g, or 20m 2 / g to 200m 2 / g; particles comprising SiO2, ZrO2 and mixtures thereof, especially mixtures thereof.
[0168] If desired, the specific surface area can be determined according to the method suggested by Brunauer, Emmet and Teller (BET) by using an apparatus (Monosorb) from Quantachrome.
[0169] The filler may comprise, contain, consist essentially of or consist of aggregated nanometer-sized particles. If desired, this may be demonstrated by transmission electron microscopy (TEM).
[0170] Once dispersed in the resin, the aggregated nanosize filler is typically maintained in the aggregated stage. That is, during the dispersion step, the particles are not broken into discrete (ie, individual) and unassociated (ie, non-agglomerated, non-aggregated) particles.
[0171] Agglomerated fillers and methods of their production and surface treatment are described, for example, in US 6,730,156 (Wu et al.) and US 6,730,156 (Windisch et al.).
[0172] Filler System The amount of filler used generally depends on the purpose for which the composition is to be used.
[0173] The filler system is typically present in an amount of at least 20 wt%, 30 wt% or 40 wt%; up to: 90 wt%, 85 wt% or 80 wt%; ranging from 20 wt% to 90 wt%, 30 wt% to 85 wt%, or 40 wt% to 80 wt%; the wt% being relative to the total composition.
[0174] Depending on the application, the amount of filler system is usually adjusted.
[0175] Temporary crown and bridge materials (as examples of dental compositions) generally do not contain large amounts of fillers. In these compositions, the content of fillers is generally in the range of 30% to 60% by weight relative to the total composition.
[0176] In dental filling materials (as an example of a dental composition; sometimes also called dental composites), which typically contain higher amounts of fillers than temporary crown and bridge materials, the filler content is typically in the range of 60 to 90 wt % relative to the total composition.
[0177] Lower viscosity dental filling materials (sometimes also referred to as "flowables") typically have a filler content in the range of 50% to 80% by weight relative to the total composition.
[0178] The compositions described herein may comprise additional components.
[0179] Additional components that may be present include plasticizers and adjuvants.
[0180] Plasticizers may contain hydroxyl groups, but generally do not contain polymerizable moieties.
[0181] If present, the plasticizer containing hydroxyl groups can contain two or more primary or secondary aliphatic hydroxyl groups (i.e., the hydroxyl groups are directly bonded to non-aromatic carbon atoms). The hydroxyl groups can be located at the ends, or they can be pendant to the polymer or copolymer. The molecular weight of the hydroxyl-containing organic material can be changed from very low (e.g., 32 g / mol) to very high (e.g., one million or more g / mol). Suitable hydroxyl-containing materials can have a low molecular weight, i.e., 32 g / mol to 200 g / mol, a medium molecular weight, i.e., 200 g / mol to 10,000 g / mol, or a high molecular weight, i.e., higher than 10,000 g / mol. As used herein, all molecular weights are weight average molecular weights.
[0182] Plasticizers containing hydroxyl groups may be non-aromatic in nature or may contain aromatic functional groups. Plasticizers containing hydroxyl groups may optionally contain heteroatoms in the molecular backbone, such as nitrogen, oxygen, sulfur, etc. Plasticizers may, for example, be selected from naturally occurring or synthetically prepared cellulosic materials.
[0183] Representative examples of suitable hydroxyl group-containing plasticizers include alkanols, monoalkyl ethers of polyoxyalkylene glycols, monoalkyl ethers of alkylene glycols, and other plasticizers known in the art.
[0184] Representative examples of useful plasticizers include alkylene glycols (e.g., 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,8-octanediol, 2-ethyl-1,6-hexanediol, bis(hydroxymethyl)cyclohexane, 1,18-dihydroxyoctadecane, 3-chloro-1,2-propanediol); polyhydroxyalkanes (e.g., glycerol, trimethylolethane, pentaerythritol, sorbitol) and other polyhydroxy compounds such as N,N-bis(hydroxyethyl)benzamide; 2-butyne-1,4-diol; 4,4-bis(hydroxymethyl)diphenyl sulfone; and castor oil.
[0185] Representative examples of useful polymeric hydroxyl group-containing plasticizers include polyoxyethylene and polyoxypropylene glycols, particularly polyoxyethylene and polyoxypropylene glycol diols and triols having molecular weights of 200 g / mol to 10,000 g / mol, corresponding to hydroxyl equivalent weights of 100 to 5,000 for the diols or 70 to 3,300 for the triols; polytetramethylene ether glycols of varying molecular weights, such as polytetrahydrofuran or "polyTHF"; copolymers of hydroxypropyl and hydroxyethyl acrylates and hydroxypropyl and hydroxyethyl methacrylates with other free radical polymerizable monomers such as acrylates, vinyl halogens, or styrene; copolymers containing pendant hydroxyl groups formed by hydrolysis or partial hydrolysis of vinyl acetate copolymers, polyvinyl acetal resins containing pendant hydroxyl groups; modified cellulosic polymers such as hydroxyethylated and hydroxypropylated cellulose; hydroxyl terminated polyesters; hydroxyl terminated polylactones, particularly polycaprolactones; fluorinated polyoxyethylene or polyoxypropylene glycols; and hydroxyl terminated polyalkadienes.
[0186] Blends of various hydroxyl group containing plasticizers are also included in this context.
[0187] Plasticizers are typically present in the following amounts: 0 wt % or at least 1 wt % or 5 wt %; up to 20 wt %, 15 wt % or 10 wt %; ranging from 0 wt % to 20 wt %, 1 wt % to 15 wt %, or 5 wt % to 10 wt %; the wt % being relative to the weight of the entire composition.
[0188] The composition may also contain suitable adjuvants or additives such as surfactants, rheology modifiers, retarders, stabilizers, pigments, dyes, photobleachable colorants, fluoride-releasing agents and other ingredients well known to those skilled in the art.
[0189] Surfactants that may be added include polyethylene glycol-modified siloxanes (e.g., Silwet TM type surfactants) and polyethylene glycol-modified carbosilanes (described, for example, in US 5,750,589 (Zech et al.)).
[0190] Rheology modifiers that may be added include surface modified fumed silicas as described above, organophilic phyllosilicates, modified ureas, and polyhydroxycarboxamides (e.g., Rheobyk available from Byk-Chemie, Wesel, Germany). TM type).
[0191] The retarder that may be added includes 1,2-diphenylethylene and its derivatives.
[0192] Stabilizers that can be used include, in particular, free radical scavengers such as substituted and / or unsubstituted hydroxyaromatic compounds (e.g., butylated hydroxytoluene (BHT), hydroquinone, hydroquinone monomethyl ether (MEHQ), 3,5-di-tert-butyl-4-hydroxyanisole (2,6-di-tert-butyl-4-ethoxyphenol), 2,6-di-tert-butyl-4-(dimethylamino)methylphenol or 2,5-di-tert-butylhydroquinone, 2-(2'-hydroxy-5'-methylphenyl)- 2H-benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)-2H-benzotriazole, 2-hydroxy-4-methoxybenzophenone (UV-9), 2-(2'-hydroxy-4',6'-di-tert-amyl-phenyl)-2H-benzotriazole, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-5'-methacryloyloxy-ethylphenyl)-2H-benzotriazole, phenothiazine and HALS (hindered amine light stabilizer).
[0193] Pigments and / or dyes that may be used include titanium dioxide or zinc sulfide (barium white), red iron oxide 3395, Bayferrox TM 920Z yellow, Neazopon TM Blue 807 (a copper phthalocyanine based dye) or Helio TM Fast Yellow ER. These additives can be used for individual coloring of the composition.
[0194] Examples of photobleachable colorants include Rose Bengal, Methylene Violet, Methylene Blue, Fluorescein, Eosin Yellow, Eosin Y, Ethyl Eosin, Eosin Blue, Eosin B, Erythrosin B, Erythrosin Yellow blends, Toluidine Blue, 4',5'-Dibromofluorescein, and blends thereof. Other examples of photobleachable colorants can be found in US 6,444,725 (Trom et al.).
[0195] Examples of fluoride-releasing agents include naturally occurring or synthetic fluoride minerals.These fluoride sources may optionally be treated with a surface treatment agent.
[0196] The adjuvant is typically present in an amount of at least 0%, 0.01% or 0.1% by weight; up to 15%, 10% or 5% by weight; ranging from 0% to 15%, or 0.01% to 10%, or 0.1% to 5% by weight; the % by weight being relative to the weight of the entire composition.
[0197] The compositions described herein may contain the following amounts of the respective components:
[0198] a) polymerizable component A1: 3% to 50% by weight,
[0199] b) polymerizable component A2: 0% to 60% by weight,
[0200] c) Initiator system: 0.1 wt % to 4 wt %,
[0201] d) Filler system: 20 wt% to 90 wt%,
[0202] e) Plasticizer: 0 wt % to 20 wt %,
[0203] f) Adjuvant: 0 wt% to 15 wt%,
[0204] Weight % is relative to the weight of the entire dental composition.
[0205] The compositions described herein may also contain the following amounts of the respective components:
[0206] a) polymerizable component A1: 5% to 40% by weight,
[0207] b) polymerizable component A2: 1% to 50% by weight,
[0208] c) Initiator system: 0.2 to 3% by weight,
[0209] d) Filler system: 30 wt% to 85 wt%,
[0210] e) Plasticizer: 1 to 15 wt %,
[0211] f) Adjuvant: 0.01 wt% to 10 wt%,
[0212] Weight % is relative to the weight of the entire dental composition.
[0213] The compositions described herein may also contain the following amounts of the respective components:
[0214] a) polymerizable component A1: 8% to 30% by weight,
[0215] b) polymerizable component A2: 5% to 40% by weight,
[0216] c) Initiator system: 0.3 wt % to 2 wt %,
[0217] d) Filler system: 40% to 80% by weight,
[0218] e) Plasticizer: 5 to 10 wt %,
[0219] f) Adjuvant: 0.1 wt% to 5 wt%,
[0220] Weight % is relative to the weight of the entire dental composition.
[0221] Certain embodiments of the compositions may also be characterized by the following physical-mechanical properties, alone or in combination, after hardening:
[0222] a) Flexural strength (FS): 140 MPa*s to 200 MPa*s, determined according to ISO 4049 (2019);
[0223] b) E-modulus (EM): 4 GPa to 16 GPa, determined according to ISO 4049 (2019);
[0224] c) Depth of cure (DoC): 3 mm to 7 mm, determined according to ISO 4049 (2019);
[0225] d) Bonding disc shrinkage-strain (SHR): 1.50% to 1.80%;
[0226] e) radial tensile strength (DTS): 75 to 100, determined according to ISO 7489 (2019);
[0227] f) Cusp deflection (Cusp-D): <12μm.
[0228] Certain embodiments of the compositions are characterized by the following physical-mechanical properties, alone or in combination, after hardening:
[0229] a) Flexural strength (FS): 150 MPa*s to 200 MPa*s, determined according to ISO 4049 (2019);
[0230] b) E-modulus (EM): 4 GPa to 10 GPa or 12 GPa to 16 GPa, determined according to ISO 4049 (2019);
[0231] c) Depth of cure (DoC): 4 mm to 6 mm, determined according to ISO 4049 (2019);
[0232] d) Bonding disc shrinkage-strain (SHR): 1.55% to 1.75%;
[0233] e) radial tensile strength (DTS): 80 to 100, determined according to ISO 7489 (2019);
[0234] a) Cusp-D: 8 to 11.
[0235] The following combinations of physical-mechanical properties are sometimes preferred: a) and b); a) and c); a), b) and c); a), c) and f; a), c) and d).
[0236] Certain embodiments of the compositions may also be characterized by the following physical-mechanical properties, alone or in combination, prior to hardening:
[0237] a) Viscosity: 5 Pa*s to 100 Pa*s at 23°C and a shear rate of 100 s-1,
[0238] b) pH value: 6 to 8;
[0239] c) It can be hardened within 10 minutes after irradiation with light with a wavelength in the range of 400nm to 700nm.
[0240] For flowable composites, the following combinations of physical-mechanical properties are sometimes preferred: a) and b) or a) and c).
[0241] A low viscosity can be advantageous because it allows the composition to flow also within deep cavities of the prepared tooth structure that might otherwise be difficult to fill.
[0242] Since the composition generally does not contain acidic substances, the pH value is substantially in the neutral range.
[0243] All components used in the compositions described herein should be sufficiently biocompatible, that is, the compositions should not produce a toxic, deleterious, or immunological response in living tissue.
[0244] The compositions described herein generally do not contain the following components, alone or in combination: 5 wt % or more of low boiling point solvents (e.g., boiling point below 150° C. at ambient pressure); 2 wt % or more of Bis-GMA or bisphenol A partially derived components; 2 wt % or more of polymerizable components containing an acidic moiety.
[0245] The compositions described herein can be obtained by combining (including mixing and kneading) the individual components of the composition, preferably under "safe light" conditions. If necessary, a speed mixer can be used.
[0246] The resulting composition can be hardened within an acceptable time frame, such as less than 10 minutes or less than 5 minutes or less than 2 minutes, and to a sufficient depth using visible light source equipment already available to practitioners.
[0247] Additional embodiments of the present invention include:
[0248] Implementation 1
[0249] The composition may comprise, consist essentially of, or consist of:
[0250] a) an amount of 3% to 50% by weight of a polymerizable component A1,
[0251] b) a polymerizable component A2 in an amount of 0% to 60% by weight,
[0252] c) an initiator system in an amount of 0.1% to 4% by weight, the initiator system comprising a ketone sensitizer and an amine donor,
[0253] d) a filler system comprising nanosized particles in an amount of 20% to 90% by weight,
[0254] e) a plasticizer in an amount of 0% to 20% by weight,
[0255] f) an adjuvant in an amount of 0% to 15% by weight,
[0256] The composition does not contain a component containing a bisphenol A moiety in an amount of 5 wt % or more, the wt % being relative to the weight of the entire composition.
[0257] Implementation 2
[0258] The composition may comprise, consist essentially of, or consist of:
[0259] a) an amount of 5% to 40% by weight of a polymerizable component A1,
[0260] b) a polymerizable component A2 characterized by the following formula:
[0261] A n BA m
[0262] wherein A is an ethylenically unsaturated group,
[0263] B is selected from (i) a linear or branched C1 to C2 optionally substituted by a halide or OH 12 (ii) C6 to C alkyl, optionally substituted by halogen or OH 12aryl, or (iii) an organic group having 4 to 20 carbon atoms bonded to one another via one or more ether, thioether, ester, thioester, thiocarbonyl, amide, carbamate, carbonyl and / or sulfonyl bonds,
[0264] m and n are independently selected from 0, 1, 2, 3, 4, 5 or 6, provided that n+m is greater than 0,
[0265] The amount is 1 wt % to 50 wt %,
[0266] c) an initiator system in an amount of 0.1% to 4% by weight, the initiator system comprising a ketone sensitizer and an amine donor,
[0267] d) a filler system comprising nanosized silica particles in an amount of 20% to 90% by weight,
[0268] e) a plasticizer in an amount of 0% to 20% by weight,
[0269] f) an adjuvant in an amount of 0% to 15% by weight,
[0270] The composition does not contain a bisphenol A-containing component in an amount of 5% by weight or more,
[0271] Weight % is relative to the weight of the entire composition.
[0272] Implementation 3
[0273] The compositions described herein may comprise, consist essentially of, or consist of:
[0274] a) an amount of 3% to 50% by weight of a polymerizable component A1,
[0275] b) a polymerizable component A2 in an amount of 5% to 60% by weight,
[0276] c) an initiator system in an amount of 0.1% to 4% by weight, the initiator system comprising a ketone sensitizer and an amine donor,
[0277] d) a filler system comprising nanosized particles in an amount of 60% to 90% by weight,
[0278] e) a plasticizer in an amount of 0% to 20% by weight,
[0279] f) an adjuvant in an amount of 0% to 15% by weight,
[0280] Weight % is relative to the weight of the entire composition.
[0281] Implementation 4
[0282] The compositions described herein may comprise, consist essentially of, or consist of:
[0283] a) an amount of 3% to 50% by weight of a polymerizable component A1,
[0284] b) a polymerizable component A2 in an amount of 0% to 60% by weight,
[0285] c) an initiator system in an amount of 0.1% to 4% by weight, the initiator system comprising a ketone sensitizer and an amine donor,
[0286] d) a filler system comprising nanosized particles in an amount of 50% to 80% by weight,
[0287] e) a plasticizer in an amount of 0% to 20% by weight,
[0288] f) an adjuvant in an amount of 0% to 15% by weight,
[0289] Weight % relative to the weight of the entire composition, the composition at 23 ° C and 100s -1 The viscosity is between 5 Pa*s and 100 Pa*s.
[0290] The composition is generally provided to the practitioner under sanitary conditions. During storage, the composition is generally packaged in a suitable packaging and / or delivery device.
[0291] One possibility to achieve this involves packaging or storing the composition in a sealed container.
[0292] Suitable containers may have a front end and a rear end, a piston capable of moving in the container, and a nozzle or cannula for delivering or dispensing the composition located in the container. The container generally has only one compartment or reservoir.
[0293] The volume of the container is typically in the range of 0.1 ml to 100 ml, or 0.5 ml to 50 ml, or 1 ml to 30 ml.
[0294] Suitable disposable containers may have a volume in the range of 0.1 ml to 2 ml. This is the volume typically required for a single administration protocol. Such containers are typically used only once (e.g., disposable packaging).
[0295] The composition can be dispensed from the container by moving the piston in the direction of the nozzle. The piston can be moved manually or with the aid of an applicator or applicator designed to receive the container, such as an applicator having a caulking gun design.
[0296] Examples of containers that can be used include compressed capsules, syringes, and screw-tubes.
[0297] The capsule generally has a cylindrical housing with a front end and a rear end and a nozzle. The rear end of the housing is generally sealed by a movable piston. Typically, an applicator with a movable plunger (e.g., an applicator in the shape of a caulking gun) is used to dispense the dental composition from the capsule or container.
[0298] Examples of suitable bladders or containers are described in US 5,624,260 (Wilcox et al.), EP 1 340 472 A1 (Centrix), US 2007 / 0172789 A1 (Mueller et al.) and US 5,865,803 (Major). Other suitable containers are exemplified in US 5,927,562 (Hammen et al.) and US 2011 / 151403 A1 (Pauser et al.).
[0299] It is advantageous if the container used comprises a nozzle of a certain shape and size, which allows an easy and safe application of the composition onto the soft tooth tissue surrounding the tooth to be restored, also in the vicinity of the interdental area.
[0300] The smaller the diameter of the nozzle, the easier it is to place the nozzle into the area between the two teeth. However, a small diameter nozzle may result in an increase in the extrusion force required to dispense the composition out of the device. Therefore, not all cannula sizes and diameters are equally suitable. It has been found that a device with a nozzle or cannula having an outer diameter in the range of 0.6 mm to 1.3 mm and an inner diameter in the range of 0.2 mm to 0.9 mm is particularly useful.
[0301] Another embodiment of the invention relates to a kit comprising at least two, three, four, five, six or more compositions which differ from each other at least in their color.As mentioned above, the compositions are typically stored in containers.
[0302] The compositions described herein are particularly useful in the dental and orthodontic fields.
[0303] The composition may be used as or for producing a dental restoration.Dental restorations are typically produced outside the patient's mouth and inserted later in a processing step.
[0304] Examples of dental restorations include direct restorative materials (eg, anterior and posterior restorations), prostheses, veneers, artificial crowns, artificial teeth, dentures, and the like.
[0305] As used herein, the term "prosthesis" refers to a composite that is shaped and polymerized for its ultimate use (eg, as a crown, bridge, veneer, inlay, onlay, etc.) prior to placement adjacent to a tooth.
[0306] When applying the dental material to the teeth, the teeth may optionally be pretreated with a primer such as a dentin or enamel adhesive by methods known to those skilled in the art.
[0307] More specifically, the composition can be used to treat hard dental tissue in the mouth of a mammal, particularly a human.
[0308] This approach typically involves the following steps:
[0309] a) contacting the composition described herein with the surface of hard tooth tissue
[0310] b) hardening the composition.
[0311] More particularly, the method may comprise the following steps:
[0312] c) applying the dental composition to the surface of the hard tooth tissue; if desired, the surface of the hard tooth tissue can be an etched surface (e.g., with phosphoric acid) or a non-etched surface,
[0313] d) optionally spreading the dental composition onto the film, preferably using a stream of air,
[0314] e) Radiation curing of dental compositions.
[0315] In particular, the composition can be used as a composite filling material, a cavity liner, a fixing material for an orthodontic appliance, or a sealant.
[0316] The term "composite filling material" refers to a filling dental composition. Dental composites are commonly used to repair missing tooth structure in a patient's mouth.
[0317] "Cavity liner" refers to a composition used to protect the dental pulp prior to the application of a composite filling material or dental restoration.
[0318] As used herein, the term "sealant" refers to a lightly filled dental composite material that cures after being placed adjacent to a tooth. Sealants are typically applied to back teeth and form a protective cap over the enamel of the tooth.
[0319] In a preferred aspect, the dental material is a low viscosity dental filling material.
[0320] In further embodiments, the dental compositions described herein are used to produce dental mill blanks.
[0321] Dental mill blanks may be produced by placing a curable composition in a mould followed by a curing step.
[0322] In another embodiment, the dental composition is used as a resin in a layer-by-layer manufacturing process for producing three-dimensional objects, such as dental articles, for example by applying 3D printing techniques.
[0323] The present invention also relates to a kit comprising the composition described herein and the following items, alone or in combination: a dental adhesive; a dental primer; a dispensing device; a polishing device; a dental curing light; and optionally instructions for use.
[0324] Dental adhesives are typically acidic dental compositions with relatively low viscosity (e.g., 0.01 Pa*s to 3 Pa*s at 23°C). Dental adhesives interact directly with the enamel or dentin surface of the teeth. Dental adhesives are typically one-part compositions, are radiation curable, and contain an ethylenically unsaturated component having an acidic moiety, an ethylenically unsaturated component not having an acidic moiety, water, a sensitizer, a reducing agent, and additives.
[0325] Examples of dental adhesives are described in US 2020 / 0069532 A1 (Thalacker et al.) and US 2017 / 0065495 A1 (Eckert et al.). Dental adhesives are also commercially available, such as 3M TM Scotchbond TM Universal (3M Oral Care).
[0326] Suitable dental primers are described in US 6,126,922 (Rozzi et al.) and WO 00 / 69393A1 (3M). Dental primers are also commercially available, for example from 3M TM Transbond TM XT Primer (3M OralCare).
[0327] Suitable polishing equipment includes rubber cuss, polishing paste and polishing disc. Polishing devices are also commercially available, such as Soflex TM Plate (3M Oral Care).
[0328] Suitable dental curing lights are described in US 10,758,126 B2 (Geldmacher et al.) or US 10,231,810 B2 (Gramann et al.). Dental curing lights are also commercially available, for example from 3M TM Elipar TM S10 or 3M TM Elipar TM DeepCureS LED curing light (3M Oral Care).
[0329] Suitable dispensing devices are described in US 2021 / 113301 A1 (Pauser et al.). Dispensing devices are also commercially available, for example from 3M TM Capsule dispenser (3M Oral Care).
[0330] The instructions for use describe how the dental composition should be used in daily practice, for example outlining the application steps and curing conditions.
[0331] The entire disclosure of the patents, patent documents and publications cited herein are incorporated by reference as a whole, as if each was incorporated separately. Various modifications and changes to the present invention will be apparent to those skilled in the art without departing from the scope and spirit of the present invention. The above specifications, examples and data provide a description of the manufacture and use of the composition of the present invention and the method of the present invention. The present invention is not limited to the embodiments disclosed herein. It will be appreciated by those skilled in the art that many alternative embodiments of the present invention may be prepared without departing from the spirit and scope of the present invention.
[0332] The following examples are given to illustrate the present invention.
[0333] Example
[0334] Unless otherwise stated, all parts and percentages are based on weight, all water is deionized water, and all molecular weights are weight average molecular weights (g / mol). In addition, unless otherwise stated, all experiments were performed under ambient conditions (23° C.; 1013 mbar). In addition, almost all process steps were performed under a dry air atmosphere.
[0335] method
[0336] pH
[0337] If desired, the pH of the composition can be determined as follows: pH sensitive paper (Carl Ross TM Carl Roth TM company). Wet a pH-sensitive paper strip. Place a small portion of the composition to be tested on the wetted pH-sensitive paper. After 5 seconds, determine the color change of the pH-sensitive paper.
[0338] Particle size distribution (non-nano-sized particles)
[0339] If desired, the particle size distribution can be determined by light scattering, for example using the device Horiba (Horiba, JP).
[0340] The light scattering particle size analyzer illuminates the sample with a laser and analyzes the intensity fluctuations of the light scattered from the particles at an angle of 173 degrees. The instrument can calculate the particle size using the photon correlation spectroscopy (PCS) method. PCS uses the fluctuating light intensity to measure the Brownian motion of particles in a liquid. The particle size is then calculated as the diameter of a sphere moving at the measured speed.
[0341] The intensity of light scattered by a particle is proportional to the sixth power of the particle size. The Z-average size or cumulative mean is the average value calculated from the intensity distribution and the calculation is based on the assumption that the particles are unimodal, monodisperse and spherical. The correlation function calculated from the fluctuating light intensity is the intensity distribution and its mean. The mean of the intensity distribution is calculated based on the assumption that the particles are spherical. The Z-average size and the intensity distribution mean are more sensitive to larger particles than to smaller particles.
[0342] The volume distribution gives the percentage of the total volume of particles that corresponds to particles in a given size range. The volume average size is the size of the particles corresponding to the mean of the volume distribution. Since the volume of a particle is proportional to the cube of the diameter, this distribution is less sensitive to larger particles than the Z-average size. Therefore, the volume average is usually a smaller value than the Z-average size. In the context of this document, the Z-average size is referred to as the "average particle size".
[0343] Particle size distribution (nano-sized particles)
[0344] The measurement of nanoparticle size is preferably based on the TEM (transmission electron microscopy) method, whereby the population is analyzed to obtain the average particle size. The preferred method for measuring particle size can be described as follows:
[0345] The approximately 80 nm thick sample was placed on a 200 mesh copper grid with a carbon stabilized polyvinyl acetate substrate (SPI Supplies-Structure Probe, Inc., West Chester, PA). Transmission electron micrographs (TEM) were taken at 200 KV using a JEOL 200CX (JEOL, Ltd., Akishima, Japan, and sold by JEOL USA, Inc.). The overall size of approximately 50-100 particles can be measured and the average diameter determined.
[0346] Flexural Strength (FS)
[0347] If desired, the measurement of flexural strength can be carried out according to ISO 4049 (2019) using a universal testing machine (Zwick Z010, crosshead speed 1 mm / min). Flexural strength is usually given in MPa.
[0348] E-modulus (EM)
[0349] If desired, EM can be determined according to ISO 4049(2019) and given in [GPa].
[0350] Bonding disc shrinkage-strain (SHR)
[0351] If desired, the bond disc shrinkage-strain can be determined according to the Watts protocol described in more detail in: Dent. Mater. 1991, 7, 281-287. Unit: [%].
[0352] Depth of Cure (DoC)
[0353] The depth of cure (i.e., depth of cure) was determined according to ISO 4049 (2019) by filling the paste sample into a cylindrical metal curing mold (8 mm deep, 4 mm diameter) and TM Trilight Standard (800mW / cm 2 (3M Oral Care) The samples were cured for 40 seconds for analysis. The cured samples were removed from the mold and after curing for less than about one minute, the uncured paste was scraped off the samples with a plastic applicator. The results are reported as the average of three replicates.
[0354] Refractive index (n D 20 )
[0355] If desired, the refractive index can be measured with a Kruess AR 4D device (refractometer according to the Abbe measurement principle).The refractive index is typically measured at 20.0°C at a wavelength of 589 nm.
[0356] Viscosity (η)
[0357] If desired, viscosity can be measured with a Physica MCR 301 (Anton Paar German GmbH, Ostfildern-Scharnhausen, Germany). Monomers were tested at 23.0°C with a shear rate of 100 / s using a 25 mm / 1° cone / plate system. Flowable composites can be measured at 25.0°C with a 15 mm plate / plate system and a gap of 0.2 mm at a shear rate of 100 / s.
[0358] Cusp-D
[0359] If desired, cusp deflection can be measured as follows:
[0360] A slot was machined in a rectangular 15×10×8 mm aluminum block. The slot was 8 mm long, 4.0 mm deep, and 4.0 mm wide, and was located 2 mm from the edge, thus forming a 4 mm wide aluminum cusp adjacent to a 4 mm wide cavity containing the dental composition being tested. A linear variable displacement transducer (model GT 1000, used with an E309 analog amplifier, both from RDP Electronics, UK) was positioned to measure the displacement of the tooth tip when the dental composition was light cured at room temperature. Prior to testing, the cusp was calibrated using a Rocatec TM Plus Special Surface with Sandblasting Material (3M OralCare) The slots in the aluminum block were sandblasted and the RelyX TM Ceramic primer (3M OralCare) and finally with dental adhesive Scotchbond TM Universal (3M OralCare) Processing.
[0361] The slot was completely filled with the paste sample, which was equal to approximately 250 mg of material. The material was cured with a dental curing light (Elipar TM S10, 3M Oral Care) was irradiated for 1 minute with the dental curing light positioned close (about 2 mm) to the material in the slot, and the displacement of the tooth tip in microns was recorded 9 minutes after the light was turned off.
[0362] Radial Tensile Strength (DTS)
[0363] If desired, DTS can be measured as follows:
[0364] The paste sample was injected into a 4 mm (inner diameter) glass tube; the tube was capped with a silicone rubber stopper; and then heated at approximately 2.88 kg / cm 2 The tube was compressed axially for 5 minutes. TM The samples were light cured for 4*20 s using a DeepCure dental curing light (3M Oral Care).
[0365] The cured samples were then cut with a diamond saw to form 2.5 mm long cylindrical plugs for measuring compressive strength. The plugs were stored in deionized water at 36° C. for about 24 hours prior to testing. Measurements were made on a Zwick / Roell universal tester (Zwick / Roell GmbH & Co. KG, Ulm, Germany) at a crosshead speed of 1 mm / min with a 10 kilonewton (kN) load cell according to ANSI / ADA specification 27.
[0366] Composition
[0367] abbreviation
[0368] The names and / or structures of the components used are given in Table 1.
[0369]
[0370]
[0371]
[0372]
[0373]
[0374] Table 1; CE represents comparative examples, IE represents embodiments of the present invention.
[0375] Synthetic compound (A)
[0376] Compound (A) can be prepared as follows:
[0377] General Procedure 1: Synthesis of alkoxylated intermediates using, for example, ethylene carbonate (EC)
[0378] Under a protective N2 atmosphere, a phenolic compound (e.g., resorcinol) and glycidyl phenyl ether (1 equivalent / phenolic OH group) and a basic catalyst (e.g., KOH or NaOH or KOtBu, at least 3 mol% relative to 1 phenolic OH group) are stirred at a temperature of at least 100°C until the epoxy groups are completely reacted (via the reaction in CD3OD). 1 H NMR measurement). Ethylene carbonate is then added (at least 1 ethylene carbonate per 1 initial phenolic OH group) and the mixture is stirred at a temperature of at least 140°C until the ethylene carbonate has reacted completely (via 1H NMR detection). The two reaction steps can be carried out sequentially as a one-pot reaction or separately as two separate reactions. The synthesis of the alkoxylated intermediate can be carried out as a classical batch reaction (pressureless or pressurized) or continuously under pressure using a flow reactor.
[0379] The reaction mixture was then cooled to about 80°C and 130 wt% of 2N NaOH solution (relative to theoretical yield) was added. The mixture was heated to reflux for at least 2 hours so that the carbonate in the EO side chain was hydrolyzed (via 1 HNMR detection). The mixture is cooled to RT and diluted with 200 wt % of toluene or ethyl acetate (relative to theoretical yield). The organic phase is separated and extracted with water several times. Then 10 wt % of Na2CO3 and 10 wt % of charcoal (each relative to theoretical yield) are added to the organic phase, and the mixture is stirred overnight under air. After filtering from Na2CO3 / charcoal, the filtrate is filtered again through 20 wt % of neutral alumina (relative to theoretical yield) and the solvent is stripped from the filtrate in vacuum. The yield of the ethoxylated intermediate is about 90%.
[0380] General procedure 2: Esterification of alkoxylated intermediates with, for example, methacrylic acid (MA)
[0381] To the ethoxylated intermediate in, for example, hexane and / or cyclohexane and / or toluene, BHT and / or HQME, optional methylene blue and / or PTZ, for example methanesulfonic acid or H2SO4 as a catalyst and for example methacrylic acid are added. Water is removed using a Dean Starck apparatus under reflux. After the reaction is complete, the crude reaction mixture is extracted at least twice with an aqueous NaOH solution (4N or 2N), then washed at least once with water, optionally dried over anhydrous Na2SO4. After filtering, the filtrate is filtered again through neutral alumina. At least 100ppm of BHT and 100ppm of HQME are added to the filtrate. The solvent is then stripped under vacuum while air is bubbled through the crude sample. The yield of the final monomer is about 90%.
[0382] Synthesis of ERGP-MA (Comparative Example 1) :
[0383] ERGP-MA was synthesized according to WO 2012 / 106083 A1 (3M Company (3M)), p. 45.
[0384] Synthesis of ERGP-A (Comparative Example 2) :
[0385] ERGP-A was synthesized according to WO 2012 / 106083 A1 (3M Company (3M)), page 45.
[0386] Synthesis of RGP2.2EO-DMA (Example 1 of the Present Invention) :
[0387] According to general procedure 1, 25.0 g of R, 68.6 g of GP and 79.9 g of EC were reacted using KOtBu as a catalyst. 112 g of RGP2.2EO (225 mmol, 98.9%) were isolated as a light yellow liquid. According to general procedure 2, 49.9 g of RGP2.2EO, 25.8 g of MA, 94.7 mg of HQME, 3.80 mg of PTZ and 2.30 g of MSA were reacted using cyclohexane:toluene=92.5:7.50 as a solvent. 58.5 g of RGP2.2EO-DMA (92.2 mmol, 92.2%) were isolated as a light yellow oil: η=5.5 Pa*s, n D 20 =1.542.
[0388] Synthesis of RGP3.3EO-DMA (Example 2 of the Present Invention) :
[0389] According to General Procedure 1, 60.0 g of R, 165 g of GP and 288 g of EC were reacted using KOH as a catalyst. 290 g of RGP3.3EO (494 mmol, 90.7%) were isolated as a light yellow liquid. According to General Procedure 2, 96.0 g of RGP3.3EO, 43.7 g of MA, 175 mg of HQME, 7.00 mg of PTZ and 4.20 g of MSA were reacted using cyclohexane:toluene=70.0:30.0 as solvent. 109 g of RGP3.3EO-DMA (140 mmol, 91.0%) were isolated as a light yellow oil: η=3.8 Pa*s, n D 20 =1.538.
[0390] Synthesis of RGP3.4EO-DMA (Example 3 of the Present Invention) :
[0391] According to general procedure 1, 25.0 g of R, 68.6 g of GP and 120 g of EC were reacted using KOtBu as catalyst. 120 g of RGP3.4EO (205 mmol, 90.2%) were isolated as a light yellow liquid. According to general procedure 2, 109 g of RGP3.4EO, 49.8 g of MA, 199 mg of HQME, 8.00 mg of PTZ and 4.80 g of MSA were reacted using cyclohexane:toluene=70.0:30.0 as solvent. 126 g of RGP3.4EO-DMA (180 mmol, 93.3%) were isolated as a light yellow oil: η=3.6 Pa*s, n D 20 =1.538.
[0392] Synthesis of RGP3.8EO-DMA (Example 4 of the Present Invention) :
[0393] According to General Procedure 1, 20.0 g of R, 54.9 g of GP and 118 g of EC were reacted using KOH as a catalyst. 102 g of RGP3.8EO (175 mmol, 96.3%) were isolated as a light yellow liquid. According to General Procedure 2, 102 g of RGP3.8EO, 45.6 g of MA, 185 mg of HQME, 7.40 mg of PTZ and 6.30 g of MSA were reacted using cyclohexane:toluene=70.0:30.0 as solvent. 118 g of RGP3.8EO-DMA (165 mmol, 93.4%) were isolated as a light yellow oil: η=3.3 Pa*s, n D 20 =1.538.
[0394] Synthesis of BCGP2.5EO-DMA (Example 5 of the Present Invention) :
[0395] According to general procedure 1, 33.4 g of BC, 63.7 g of GP and 69.6 g of EC were reacted using KOH as a catalyst. 114 g of BCGP2.5EO (192 mmol, 95.5%) were isolated as a light yellow liquid. According to general procedure 2, 114 g of BCGP2.5EO, 49.5 g of MA, 204 mg of HQME, 8.20 mg of PTZ and 7.00 g of MSA were reacted using cyclohexane:toluene=70.0:30.0 as solvent. 130.4 g of BCGP2.5EO-DMA (179 mmol, 93.5%) were isolated as a light yellow oil: η=5.3 Pa*s, n D 20 =1.535.
[0396] Synthesis of PhloGP6EO-TMA (Example 6 of the Present Invention) :
[0397] According to General Procedure 1, 20.2 g of Phlo, 72.6 g of GP and 141 g of EC were reacted using KOH as a catalyst. 119 g of PhloGP6EO (142 mmol, 88.4%) were isolated as a light yellow liquid. According to General Procedure 2, 70.6 g of PhloGP6EO, 32.5 g of MA, 516 mg of HQME, 15.5 mg of PTZ and 3.09 g of MSA were reacted using cyclohexane:toluene=20.0:80.0 as a solvent. 83.2 g of PhloGP6EO-TMA (79.6 mmol, 94.8%) were isolated as a light yellow oil: η=14.6 Pa*s, n D 20 =1.538.
[0398] Synthesis of PhloGP6EO-TA (Example 7 of the Present Invention) :
[0399] According to General Procedure 1, 20.2 g of Phlo, 72.6 g of GP and 141 g of EC were reacted using KOH as a catalyst. 119 g of PhloGP6EO (142 mmol, 88.4%) were isolated as a light yellow liquid. According to General Procedure 2, 87.1 g of PhloGP6EO, 33.6 g of AA, 603 mg of HQME, 18.1 mg of PTZ and 3.70 g of MSA were reacted using cyclohexane:toluene=20.0:80.0 as a solvent. 95.6 g of PhloGP6EO-TA (95.3 mmol, 92.0%) were isolated as a light yellow oil: η=30.3 Pa*s, n D 20 =1.543.
[0400] Some properties of the synthesized components are given in Table 2.
[0401] Components Molecular weight Viscosity (Pa*s) Refractive Index CE1 634.7 9.4 1.542 CE2 606.7 18.8 1.547 IE1 634.7 5.5 1.542 IE2 695.1 3.8 1.538 IE3 703.0 3.6 1.538 IE4 716.7 3.3 1.538 IE5 727.41 5.3 1.535 IE6 1045.2 14.6 1.538 IE7 1003.1 30.3 1.543
[0402] Table 2
[0403] The polymerizable components of the present invention are low in viscosity, have a sufficiently high refractive index and do not contain bisphenol-A moieties.
[0404] Synthesis of photocurable one-component compositions
[0405] Some of the synthesized compounds were used to produce (dental) compositions. The compositions produced and tested with regard to their mechanical properties are given in the following Table 3. In Table 3, the values for components a) to i) represent the weight % of the respective component in the corresponding formulation.
[0406] General Procedure A :
[0407] The initiator system components are dissolved in the monomers at a temperature not higher than 50°C (depending on the intrinsic viscosity of the monomers used) under magnetic stirring and protected from light.
[0408] General Procedure B :
[0409] The initiator system components were dissolved in the monomers according to General Procedure A. The filler was mixed with the mixture of the initiator system and monomers in batches under light protection and using a double-arm kneader. The amount of filler was manually determined based on the desired processing properties of the dental composition. The curing lamp was then heated to 100°C using an 800 mW halogen curing lamp (3M Oral Care, Elipar TM The dental compositions were light cured using Trilight and tested according to the corresponding measurements listed above. The corresponding values are given in Table 3.
[0410] Composition A contains component a) but does not contain compound (A) according to the invention. In the following Table 2, compound (A) is represented by components b) to e). Therefore, composition A can be considered as a comparative example, while compositions B to E can be considered as examples of the invention.
[0411]
[0412]
[0413] Table 3; “*” Embodiment of the present invention
[0414] It can be seen that the composition containing the compound (A1) according to the present invention is excellent in certain properties (e.g., FS, EM, DTS) or shows sufficient properties at a high level in other aspects (e.g., DoC, SHR, Cusp-D) compared to the composition not containing the compound (A1) according to the present invention.
Claims
1. A dental composition comprising a) resin matrix, b) initiator system, c) Filler system, The resin matrix comprises a polymerizable component A1 characterized by any one of the following formulas (I), (II) or (III) in X = independently selected from H, alkyl, I, Br, Cl, Z = independently selected from H, CH3, CH2OH, n, m = integers independently selected from the range of 1 to 10, (m+n)=1 to 10, R = independently selected from H, CH3, in X = independently selected from H, alkyl, I, Br, Cl, Z = independently selected from H, CH3, CH2OH, k, n, m = integers independently selected from the range of 1 to 10, (k+m+n)=1 to 15, R = independently selected from H, CH3, and mixtures thereof.
2. The dental composition according to claim 1, wherein the polymerizable component A1 is selected from in m, n, k = integers independently selected from the range of 1 to 10, and (m+n)=1 to 10, or (m+n+k)=1 to 15, and mixtures thereof.
3. The dental composition according to any one of the preceding claims, wherein the polymerizable component A1 is characterized by the following properties, alone or in combination: a) Viscosity: 2Pa*s to 40Pa*s, at 23°C and 100s -1 At a shear rate of 25 mm / 1° cone / plate system was used; b) Refractive index: 1.520 to 1.565, measured at 20.0° C. at a wavelength of 589 nm.
4. The dental composition according to any of the preceding claims, the resin matrix comprising one or more polymerizable components A2 different from the polymerizable component A1, the polymerizable component A2 preferably being characterized by the following formula: A n BA m wherein A is an ethylenically unsaturated group, B is selected from (i) a linear or branched C1 to C2 optionally substituted by halogen or OH 12 (ii) C6 to C alkyl, optionally substituted by halogen or OH 12 aryl, or (iii) an organic group having 4 to 20 carbon atoms bonded to one another via one or more ether, thioether, ester, thioester, thiocarbonyl, amide, carbamate, carbonyl and / or sulfonyl bonds, m and n are independently selected from 0, 1, 2, 3, 4, 5 or 6, with the proviso that n+m is greater than 0.
5. A dental composition according to any one of the preceding claims, wherein the initiator system comprises a photoinitiator system, preferably comprising a ketone sensitizer, an amine donor and optionally iodine. Salt-based photoinitiator systems. 6 . The dental composition according to claim 1 , wherein the filler system comprises nanosized particles and is present in an amount of 20% to 90% by weight relative to the weight of the entire composition.
7. The dental composition according to one of the preceding claims, comprising the following amounts of the components: a) polymerizable component A1: 3% to 50% by weight, b) polymerizable component A2: 0% to 60% by weight, c) Initiator system: 0.1 wt % to 4 wt %, d) Filler system: 20 wt% to 90 wt%, e) Plasticizer: 0 wt % to 20 wt %, f) Adjuvant: 0 wt% to 15 wt%, Weight % is relative to the weight of the entire composition.
8. The dental composition according to one of the preceding claims, which does not comprise the following components, alone or in combination: 5 wt% or more of a solvent having a boiling point below 150°C; bisphenol A derived components in an amount of 2% by weight or more; an amount of 2% by weight or more of a polymerizable component containing an acidic moiety, Weight % is relative to the weight of the entire composition.
9. The dental composition according to any one of the preceding claims, characterized by the following features alone or in combination before hardening: a) Viscosity: 5Pa*s to 100Pa*s, at 25°C and 100s -1 At a shear rate of b) pH value: 6 to 8; c) It can be hardened within 10 minutes after irradiation with light with a wavelength in the range of 400nm to 700nm.
10. The dental composition according to any one of the preceding claims, characterized by the following features after hardening, alone or in combination: a) Flexural strength: 140Mpa*s to 200Mpa*s, determined according to ISO 4049(2019); b) E-modulus (EM): 4 GPa to 16 GPa, determined according to ISO 4049 (2019); c) Cure depth: 3 mm to 7 mm, determined according to ISO 4049 (2019); d) Bond disc shrinkage-strain: 1.50% to 1.80%, determined as described in the Experimental Section; e) Radial tensile strength: 75 MPa to 100 MPa, determined according to ISO 7489 (2019); f)Curve curvature: <12μm.
11. The dental composition according to any one of the preceding claims, characterized in that it comprises: a) an amount of 3% to 50% by weight of a polymerizable component A1, b) a polymerizable component A2 in an amount of 0% to 60% by weight, c) an initiator system in an amount of 0.1% to 4% by weight, the initiator system comprising a ketone sensitizer and an amine donor, d) a filler system comprising nanosized particles in an amount of 20% to 90% by weight, e) a plasticizer in an amount of 0% to 20% by weight, f) an adjuvant in an amount of 0% to 15% by weight, Weight % relative to the weight of the entire composition, The composition does not include a component containing a bisphenol A moiety in an amount of 5 wt % or more.
12. A kit comprising a dental composition according to any one of the preceding claims and the following, alone or in combination: a dental adhesive; a dental primer; a dispensing device; a polishing apparatus; a dental curing light.
13. Use of the dental composition according to any one of claims 1 to 11 for the production of dental restorations, for the production of dental mill blanks, or as resin in a laminated manufacturing process for the production of dental articles.
14. The dental composition according to any one of claims 1 to 11, for use in a method of treating hard tooth tissue in a mammal's mouth, the method comprising the steps of applying the dental composition to the surface of hard tooth tissue and hardening the dental composition.
15. Dental composition according to the preceding claim for use as composite filling material, fixing material for orthodontic appliances, cavity liner or sealant.
Citation Information
Patent Citations
Dental composition and use thereof
CN106029046A
Dental composition with high e-modulus
CN111315341A
Dental composition, method of producing and use thereof
WO2012106083A1
